Severe clinical forms of Mediterranean spotted fever: a case series from an endemic area in Bulgaria - Baymakova, Magdalena; Pekova, Liliya; Parousheva, Pavlina; Andonova, Radina; Plochev, Kamen (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Mediterranean spotted fever (MSF) belongs to Rickettsioses, the Spotted fever group (SFG). The causal agent is Rickettsia conorii conorii and the transmission to humans occurs through dog tick Rhipicephalus sanguineus bites. The aim of this study was to describe clinical and laboratory characteristics in patients with severe form of Mediterranean spotted fever admitted to Bulgarian university hospital in endemic region. Methods. A retrospective study was conducted at Stara Zagora University Hospital (Southeastern Bulgaria) between April 2015 and August 2016. During the analyzed period, 58 cases had clinical and laboratory data for MSF. Serological tests were applied for the etiological diagnosis. MSF-specific immunoglobulin (IgM) and IgG antibodies were detected in serum by indirect immunoenzyme assay (ELISA IgG/IgM, Vircell, Spain) – R. conorii ELISA IgG sensitivity 85%, specificity 100% and R. conorii ELISA IgM sensitivity 94%, specificity 95%. Statistical analysis was made by MS Excel 2007 and SPSS Statistics, version 19.0. Results. Eighteen patients presented as severe forms. The predominant gender of them were males (78%) and 22% were females. The median age of the analyzed group was 55 years (range: 14–78 years). Ten patients developed hepatic disorder while 4 had neurological signs. Laboratory data showed thrombocytopenia in 15 patients, mean value of platelet (PLT) count for the whole group was 108.6 ± 53.8 × 109/L. Liver enzymes were elevated with mean value of aspartate aminotransferase (AST) 161.4 ± 90.1 IU/L and alanine aminotransferase (ALT) 163.9 ± 81.5 IU/L. Acute phase reactant as C-reactive protein (CRP) had mean value of 140.3 mg/L (range: 9–230 mg/L). Kidney function was impaired in some cases; the mean value of creatinine for the studied group was 134.7 µmol/L (range: 78–313 µmol/L) and mean value of urea was 9.6 mmol/L (range: 4.2–27.4 mmol/L). Conclusion. Bulgaria is an endemic area for tick-borne diseases. Cases of MSF are reported annually. Severe forms of MSF are not rare. Typical clinical and laboratory markers for severity should be actively searched for. Early diagnosis and proper treatment is the key to avoid complications and enable patient recovery.